Development of lyophilization cycle and effect of excipients on the stability of catalase during lyophilization - Lale, Shantanu V; Goyal, Monu; Bansal, Arvind K (International Journal of Pharmaceutical Investigation)
Introduction: The purpose of the present study was to screen excipients such as amino acids and non-aqueous solvents for their stabilizing effect on catalase, a model protein, for lyophilization. The present study also includes optimization of lyophilization cycle for catalase formulations, which is essential from the commercial point of view, since lyophilization is an extremely costly process. Materials and Methods: Activity of catalase was determined using catalase activity assay. Differential scanning calorimetry was used to determine eutectic melting temperature of the frozen catalase solution, which is essential for the optimization of lyophilization cycle. Results: When catalase was lyophilized without excipients, it was found that about 65-78% of the initial activity of catalase was lost during the lyophilization process in a concentration dependent manner. The maximum stability of catalase during lyophilization was observed at pH 7.0. Amino acids like alanine, glycine, lysine, serine and 4-hydroxy proline showed strong stabilizing effect on catalase during lyophilization by protecting catalase activity above 95%, whereas valine and cysteine hydrochloride showed destabilizing effect on catalase. Non-aqueous solvents such as dimethyl formamide, dimethyl sulphoxide, polyethylene glycol (PEG) 200, PEG 400, PEG 600 and ethylene glycol also showed destabilizing effect on catalase during lyophilization. Conclusions: In order to prevent loss of catalase activity during lyophilization of catalase, use of amino acids like alanine, glycine, lysine, serine and 4-hydroxy proline in optimum concentration is highly advisable.
Keywords: Cryoprotectants; freeze drying; lyoprotectants; protein stability